2020
DOI: 10.1177/1744806920922115
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional connectivity of the insula in a rat model of recurrent headache

Abstract: Migraine is a pain disorder accompanied by various symptoms. The insula, a “cortical hub,” is involved in many functions. Few studies have focused on the insula in migraine. We explored the resting-state functional connectivity between the insula and other brain areas in rats subjected to repeated meningeal nociception which was commonly used as animal model of migraine. Inflammatory soup was infused through supradural catheters in conscious rats. The rats were subdivided based on the frequency of the inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…The insula is often referred to as a core region of SN, a pivotal large-scale network that is associated with task processing, attention processing, and integrating of external and internal stimuli [ 28 , 29 ], as well as gating pain processing [ 30 , 31 ]. In accordance with the present results, some clinical and animal model studies have concluded that the insula is involved in regulation of headache intensity and attack frequency of migraine and other neuropathic pain [ 32 34 ]. However, a prior study [ 35 ] demonstrated contrary results in female MwoA patients during a headache-free period.…”
Section: Discussionsupporting
confidence: 92%
“…The insula is often referred to as a core region of SN, a pivotal large-scale network that is associated with task processing, attention processing, and integrating of external and internal stimuli [ 28 , 29 ], as well as gating pain processing [ 30 , 31 ]. In accordance with the present results, some clinical and animal model studies have concluded that the insula is involved in regulation of headache intensity and attack frequency of migraine and other neuropathic pain [ 32 34 ]. However, a prior study [ 35 ] demonstrated contrary results in female MwoA patients during a headache-free period.…”
Section: Discussionsupporting
confidence: 92%
“…Mental imagery is a process that integrates multisensory perception to generate a vivid mental image or experience (Di Corrado et al, 2019). TEa was found to have an increased functional connection with insula in a migraine rat model recently, which also suggested the important role of it (Jia et al, 2020). In our study, the enhanced neuronal activity in LA and TEa could not be completely reversed by topiramate.…”
Section: Discussioncontrasting
confidence: 41%
“…Similar to our results, Xiu reported WMH to be most prevalent in the frontal lobe (74.9%) followed by the parietal lobes. In our study, 14% of individuals (n = 21) with frontal lobe hyperintensities had WMH located in the insula which is an intriguing nding as the insula is a known 'cortical hub' and a key region of the salience network (17) involved in cognitive and interoceptive components of the pain experience (18) and an area known in migraine to demonstrate alterations brain functional connectivity using resting-state imaging (19)(20)(21). Furthermore, using positron emission tomography [ 11 C]HOwe(9) PBR28 imaging, Hadjikhani and collegues found increased binding of the 18 kDa translocator protein, a marker of glial activation, in individuals with migraine with aura in the bilateral insula (22).…”
Section: Discussionmentioning
confidence: 73%